Inhibitory effects of sulfide on nitrifying biomass in the anaerobic–anoxic–aerobic wastewater treatment process. Issue 2 (29th May 2013) - Zhou, Zhen; Xing, Can; An, Ying; Hu, Dalong; Qiao, Weimin; Wang, Luochun
Abstract BACKGROUND Long pipeline transportation of wastewater usually generates high concentration of sulfide; however, information on nitrification inhibition by sulfide in the anaerobic–anoxic–aerobic (AAO) process is still scarce. This study focused on how sulfide could inhibit nitrification activity in the AAO process, and the inhibitory effect of initial sulfide concentration and anaerobic exposure time on the behavior of nitrifying biomass. RESULTS The net maximum specific growth rate (μAUT‐bAUT) was, respectively, 0.06 ± 0.01 and 0.31 ± 0.03 d−1 at 15 and 20°C in a full‐scale AAO wastewater treatment plant for long‐pipeline transported wastewater. The μAUT‐bAUT was not affected by 6.2 mg L−1 sulfide under aerated condition, but reduced by 75.9% after unaerated exposure for 0.5 h. The first‐order kinetic constant of sulfide inhibition under anaerobic conditions was 0.658 h−1, and half maximal inhibition concentration of sulfide on nitrification was 36.0 and 10.0 mg L−1 after 1.0 h and 1.5 h anaerobic exposure, respectively. CONCLUSION Nitrifying biomass was sensitive to the presence of sulfide under anaerobic conditions. The inhibitory reaction of sulfide on nitrifying biomass under anaerobic conditions conformed to the first‐order kinetic reaction, while the effect of initial sulfide concentration on nitrification inhibition matched the modified Monod model. © 2013 Society of Chemical Industry